(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Advertising or advertizing in business isa form of marketing communication usedto encourage, persuade, or manipulate an audience (viewers,readers or listeners; sometimes a specific group) to take or continue to takesome action. Most commonly, the desired result is to drive consumer behaviorwith respect to a commercial offering, although political and ideologicaladvertising is also common. This type of work belongs to a categorycalled affective labor.